2012
DOI: 10.1093/europace/eus304
|View full text |Cite
|
Sign up to set email alerts
|

Complications of catheter ablation for atrial fibrillation in a high-volume centre with the use of intracardiac echocardiography

Abstract: Atrial fibrillation ablation procedures guided by ICE in a high-volume centre are associated with low rate of serious complications. The composite risk score consisting of body weight, age, gender, and complexity of procedure predicted complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
94
1
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(101 citation statements)
references
References 23 publications
3
94
1
3
Order By: Relevance
“…However, the other group of authors identified lower body weight as the only independent predictor of complications, with a 0.8% increased risk for every 10 kg of body weight reduction, most likely due to a tendency of the underweight patients to be overdosed with anticoagulant drugs during the procedure. The distribution of complication rate among patients ≤80 kg, 81-90 kg, 91-100 kg and >100 kg was 4.8%, 3.5%, 2.5% and 2.0%, respectively [133].…”
Section: Agementioning
confidence: 89%
See 2 more Smart Citations
“…However, the other group of authors identified lower body weight as the only independent predictor of complications, with a 0.8% increased risk for every 10 kg of body weight reduction, most likely due to a tendency of the underweight patients to be overdosed with anticoagulant drugs during the procedure. The distribution of complication rate among patients ≤80 kg, 81-90 kg, 91-100 kg and >100 kg was 4.8%, 3.5%, 2.5% and 2.0%, respectively [133].…”
Section: Agementioning
confidence: 89%
“…Some studies indicated that the additional ablation of complex AF substrate either with linear ablation or CFAE ablation increases procedure risk [50,53,133]. The long procedure time, prolonged catheter manipulation in the LA, a higher energy output and ablation within the coronary sinus in order to achieve transmural lesion, may all increase the risk of perforation and embolism [135].…”
Section: Agementioning
confidence: 99%
See 1 more Smart Citation
“…Monitoring of LET, periprocedural imaging with computed tomography, MRI or intracardiac echocardiography, modulation of power and duration of radiofrequency energy during ablation and mechanical esophageal displacement have been suggested as possible ways to decrease injury to the esophagus. [29][30][31][32][33][34][35][36][37] However, their roles in preventing VN injury during RFA have not been systematically studied. Further studies are therefore necessary to identify methods to safely perform AF ablation without damaging the VN.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in many laboratories, ICE is routinely used to assist transseptal puncture; therefore, no additional costs are present in such a situation. 15 An observational retrospective study has shown that some LAA morphologies, assessed by CT, may be associated with an increased risk of stroke in low-risk patients. 16 However, the association of specific LAA morphologies with an increase in the risk of thrombus development in the LAA has not been investigated.…”
Section: Discussionmentioning
confidence: 99%